2020
DOI: 10.1002/mds3.10134
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal polymers for medical applications

Abstract: The application of polymers as medical devices has steadily increased in almost all medical fields because of the versatility of these materials. Thus, research has focused both on the development of more appropriate materials for specific situations and on the modification of already useful materials for the improvement of their intrinsic properties. Modifications on this kind of materials have increased their potential uses by adapting their mechanical properties to specific needs. Moreover, biocompatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…Polymers’ versatility is also recognized in their ability to sustain drug delivery after incorporation into nanocolloidal dispersions, nanoparticle supports, or complex nanocomposites, as previously discussed. The interest becomes greater when polymers have the power to interact with drug molecules or to be grafted with functional chemical groups, initiating the antifungal activity in this route [ 198 ].…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymers’ versatility is also recognized in their ability to sustain drug delivery after incorporation into nanocolloidal dispersions, nanoparticle supports, or complex nanocomposites, as previously discussed. The interest becomes greater when polymers have the power to interact with drug molecules or to be grafted with functional chemical groups, initiating the antifungal activity in this route [ 198 ].…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%
“…Thus, polymers are promising biomaterials that can be processed to exhibit antifungal activity. Recent pursuits proposed various manners in which polymers may be adapted to these requirements by the modification of the polymeric structure with specific moieties derived from antifungal drugs, the modification of polyenes and echinocandins, the synthesis of composites with the inclusion of inorganic or organic compounds, or designing polymers as inclusion agents for various drug molecules [ 198 ]. Groups of peptide-like polymers, inspired by the activity of antimicrobial peptides, have been suggested, with activity on resistant C. albicans and other fungi strains.…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nylon-3 polymers have been proven to have significant activity against pathogenic strains of C. albicans that are resistant to conventional medication. Particularly, nylon-3 polymers with β-amino residues (βNM) in their backbone structure attracted more interest due to their resemblance to proteins that induce biocompatibility [60][61][62][63]. Moreover, such nylon-3 polymers can be easily prepared, being promising as clinical antifungal agents [60].…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…Guanidines are another class of cationic polymers that can be used as antiseptics and antimicrobials. Particularly, polyhexamethylene guanidine hydrochloride (PHMGH) was evaluated for its antifungal properties [61,[64][65][66]. Choi et al [67] reported a more potent antifungal activity of PHMGH than amphotericin B, with no hemolytic and lactate dehydrogenase release activities.…”
Section: Polymeric Materialsmentioning
confidence: 99%